Iron overload status in patients with non-transfusion-dependent thalassemia in China. (March 2022) - Huang, Yumei; Yang, Gaohui; Wang, Man; Wei, Xiaoyun; Pan, Lingyuan; Liu, Jiaodi; Lei, Yu; Peng,; Long, Liling; Lai, Yongrong; Liu, Rongrong
Background: Iron overload is one of the main factors that increase morbidity and mortality in patients with non-transfusion dependent thalassemia (NTDT). Aim: This study aimed at investigating the prevalence and severity of iron overload in Chinese NTDT patients. Methods: we analyzed serum ferritin (SF), liver iron concentration (LIC) and cardiac T2* in 178 Chinese NTDT in this cross-sectional study. Results: The median SF level was 996.00(27.15–19704.00) ng/ml and the median LIC value was 8.90(0.60–43.00) mg Fe/g dry weight (dw). The youngest patient with liver iron overload was 5 years old with 5.6 mg Fe/g dw in LIC. The median cardiac T2* was 33.06(7.46–75.08) ms. 6 patients had cardiac T2*⩽20ms. The patients with β thalassemia intermedia and HbE/β thalassemia showed a statistically significant lower Hb and higher values of SF and LIC than those of hemoglobin H disease patients. On multivariate logistic regression analysis, patients in ⩾ age 30-year old had a significant higher risk for iron overload (OR: 77.75, 95% CI: 8.76–690.49) in the age group. The detailed analysis of proportions of different LIC indicate in  > 30-year old group, 76.8% patients suffered from moderate and severe LIC. Conclusion: Our study provides a strong support for the novel findings that Chinese NTDT patients have a high prevalence of iron overload. The first assessment of MRI LIC should be performed as early as 5 years old. Then, NTDT patients  > 30 years old may suffer with a high burden of iron overload.